Allergy Bot the Intelligent Way to Predict Food Allergy - Abd Rahman, Nor Azlina; Nathan, Yogeswaran; Chin Hui, Edwin Chan (International Journal of Psychosocial Rehabilitation, 2019)
Allergy Bot is also known as Smart Allergy is a mobile application that provide smart-messaging application to let the user capture and collect crucial information about their allergies and health. By using artificial intelligent and highly developed algorithms, Allergy Bot detects which food is causing the reactions and allergic symptoms. In fact, user’s interaction with the application will help the application learn the user’s behaviours and become more personalized to the user as it also gradually improves the accuracy of the allergy prediction. As a result, Allergy Bot could help user allergies without compromising nutrition and their quality of life, thus contributing to improving user health. This paper is reviewing several existing system such as Alli App, Food Intolerance and Ada system to identify any lacking or improvement of the systems that needed to apply to the Allergy Bot framework. On top of that, users’ requirements are also gathered and analyzed to identify the features that need to be included to the framework. Allergy Bot framework is proposed based on the research on similar system and users’ requirements. Detail components of the framework are being explained.